2022
DOI: 10.3390/fermentation8030106
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Technology for Vacuum-Packaged Cooked Sausage Preservation with Potentially Postbiotic-Containing Preservative

Abstract: In this study, a potentially postbiotic-containing preservative (PPCP) was produced in an axenic fermentation system with Lacticaseibacillus paracasei DTA 83 as a natural technology alternative for vacuum-packaged cooked sausage preservation. Cooked sausage-related microorganisms were obtained during the induced spoiling process in packages by pair incubation of sausages at different temperatures. The turbidity method was used to determine the microbiota susceptibility to PPCP. A controlled in situ design was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…By consuming products made from the fermentation of Saccharomyces cerevisiae , it may be possible to limit the amount of Salmonella enterica contamination in poultry products by consuming products made from S. cerevisiae fermentation [ 218 ]. Postbiotic-containing preservatives were found to be as effective as frequently used commercial preservatives in preserving vacuum-packaged cooked sausages as natural preservation technologies [ 219 ]. Postbiotics can be used as an alternative biocontrol for the safe production of dairy products, fruits, and vegetables.…”
Section: Applications Of Postbiotics In the Food Industrymentioning
confidence: 99%
“…By consuming products made from the fermentation of Saccharomyces cerevisiae , it may be possible to limit the amount of Salmonella enterica contamination in poultry products by consuming products made from S. cerevisiae fermentation [ 218 ]. Postbiotic-containing preservatives were found to be as effective as frequently used commercial preservatives in preserving vacuum-packaged cooked sausages as natural preservation technologies [ 219 ]. Postbiotics can be used as an alternative biocontrol for the safe production of dairy products, fruits, and vegetables.…”
Section: Applications Of Postbiotics In the Food Industrymentioning
confidence: 99%
“…The ultrasonic treatment facilitated the rapid release of postbiotics from BNC into the buffalo patties. de Lima et al (2022) produced a potential PPCP by an axenic fermentation system with Lacticaseibacillus paracasei DTA 83. The results revealed that PPCP was as effective as Sodium lactate FCC85 (commercial preservative for storing vacuum-packed cooked sausages) and extended the expiry date for vacuum-packed cooked sausages higher than 90 days.…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…By consuming products made from the fermentation of Saccharomyces cerevisiae, it may be possible to limit the amount of Salmonella enterica contamination in poultry products (Chaney et al, 2022). Postbiotic-containing preservatives were found to be equally as effective as frequently used commercial preservatives in preserving vacuum-packaged cooked sausages in order to provide natural preservation technologies (de Lima et al, 2022). Postbiotics can be used as an alternative to biocontrol to make dairy products, fruits, and vegetables safe.…”
Section: Applications Of Postbiotics In Food Industrymentioning
confidence: 99%